Moderating the association between discrimination and adjustment: A Meta-analysis of ethnic/racial identity - Yip, Tiffany (Dev Psychol, 2019)
The detrimental effects of discrimination are well documented; however, the influence of ethnic/racial identity (ERI) on this association is equivocal. There is theoretical and empirical support for both protective and detrimental effects of ERI. This meta-analysis includes 53 effect sizes from 51 studies and 18,545 participants spanning early adolescence to adulthood to synthesize the interaction of ERI and discrimination for adjustment outcomes. Consistent with existing meta-analyses, discrimination was associated with compromised adjustment; further, this effect was buffered by overall ERI particularly for academic and physical health outcomes. Different ERI dimensions and adjustment outcomes revealed important patterns. ERI exploration increased vulnerabilities associated with discrimination, particularly for negative mental health and risky health behaviors. The exacerbating influence of ERI exploration was strongest at age 24 years old, and more recent publications reported weaker exacerbating effects. In contrast, ERI commitment conferred protection. A composite score of ERI exploration and commitment also conferred protection against discrimination. Sample demographics mattered. The buffering effect of ERI commitment was stronger for Latinx (compared to Asian-heritage) individuals. The buffering effect of public regard was stronger for Asian-heritage (compared to African-heritage) individuals. For positive mental health outcomes, a composite score of ERI exploration and commitment had a stronger buffering effect for Latinx (compared to African-heritage) individuals. For risky health behaviors, Latinx individuals reported a stronger buffering effect of ERI (compared to African-heritage and Asian -heritage) individuals. The current meta-analysis identifies gaps in the literature and offers suggestions for future research.